Immediate response to cigarette smoke. - Rees, P J (1982)
Using an automated method of calculating airways resistance in the body plethysmograph, we have investigated changes occurring immediately after inhalation of cigarette smoke. Decreases in specific conductance occurred by the time of the first measurement seven or eight seconds after exposure to single inhalations of cigarette smoke in 12 smokers and 12 non-smokers. Less than half of the initial change was present 40 seconds after the inhalation. Initial responses were greater in the non-smokers. Responses recurred with repeated inhalations in smokers and non-smokers. Prior administration of salbutamol and ipratropium bromide significantly inhibited the response and this inhibition appeared to be greater in non-smokers. Sodium cromoglycate inhaled as a dry powder had no effect on the response.